Colheita de Spirulina platensis via biofloculação fúngica e uso da biomassa em bioprocessos - Nazari, Mateus Torres (2021)
Microalgae can be cultivated aiming to use their biomass to produce biofuels or to obtain high value-added bioproducts. Although the production of biofuels from microalgae has numerous advantages over other feedstocks, its large-scale application is still limited by economic aspects. In this sense, studies have been aimed to reduce production costs, especially to optimize the harvesting, which is reported as one of the most limitations in third-generation biofuels. Among the techniques commonly used, bioflocculation is a promising alternative and eco-friendly method, based on its viability in terms of cost, execution, and efficiency. From a review article developed, it was verified that filamentous fungi can be used as biofloculants of microalgae due to the mutual interaction that occurred by charge differences between these microorganisms. However, there is a lacking of studies addressing applications for biomass resulting from fungal-mediated biofloculation processes, especially for bioethanol. Thus, this work aimed to implement different bioprocesses to harvest Spirulina platensis cells using Aspergillus niger biomass as a bioflocculant. Besides, the bioflocculation process was scaled-up and, from the resulting algae:fungus biomass, the aim was to produce bioethanol. These aims were divided and presented in this document in four chapters, which contain the articles resulting from this dissertation. It was possible to determine the best experimental conditions to produce Aspergillus niger biomass under submerged fermentation using two agro-industrial by-products as substrate. However, a low amylolytic activity was obtained, making it impossible to use the amylases produced by the fungus in the saccharification step. Regarding bioflocculation, Aspergillus niger biomass is a viable bioflocculant of Spirulina platensis, since all microalgal biomass was harvested in two hours in some experimental conditions, and a ~90% efficiency has been achieved without any addition of chemicals. Also, a 20-fold scale increase of the biofloculation process was studied, which resulted in a harvesting efficiency greater than 95%. Regarding bioethanol, it was not possible to produce this biofuel using the bioflocculated biomass. Therefore, further studies should evaluate methods of cell disruption and saccharification of biomasses from bioflocculation, to make it possible to produce bioethanol from this matrix. All these aspects explored in this work aimed to contribute to the sustainability of Spirulina cultivations, especially for the concept of integrated biorefinery and the United Nations Sustainable Development Goals.